Effect of innate and induced immunity on infectious bursal disease pathogenesis - A. N. Semina (Ветеринария сегодня)
Infectious bursal disease (IBD) is induced by a small non-enveloped virus, which is highly stable in the outer environment. The infectious bursal disease virus (IBDV) affects chicken’s immune system in a comprehensive and integrated manner thus destructing B-lymphocytes, attracting T-cells and activating macrophages. Being the RNA-virus, the agent is specified by high frequency of mutations, which result in the emergence of the strains with modified antigenicity and increased virulence. The molecular basis for the virus pathogenicity and exact cause of the clinical disease and death are still understudied as they are not clearly associated with the disease severity and degree of bursa of Fabricius lesions. Recent studies, however, demonstrated the role of the enhanced immune response at early stage of the infection along with increased production of cytokine storm-inducing promediators. In case of IBD, the immunosuppression is both direct consequence of specific target-cell infection and indirect consequence of the interactions occurring in the bird’s immune network. Infection with highly virulent virus strain or chicks’ infection at early age after recovery or subclinical infection results in immunosuppression with more severe consequences. Since immunosuppression induced by IBD agent is targeted mostly at B-lymphocytes, effect on the cell-mediated immunity was also demonstrated and it enhances the virus pressure on the immunocompetence of the chicks. The recent progress in avian immunology allowed for better understanding of the immunological mechanisms involved in the disease development. This review focuses on the role of the innate immunity in IBD pathogenesis as it is the first line of protection against the virus replication and can predetermine the disease outcome.